2013
DOI: 10.1152/jn.00730.2012
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal GABA-mediated and cerebellar inhibition in women with the fragile X premutation

Abstract: Abnormal GABA-mediated and cerebellar inhibition in women with the fragile X premutation. J Neurophysiol 109: 1315-1322, 2013. First published December 12, 2012 doi:10.1152/jn.00730.2012The fragile X syndrome is a mutationdriven developmental disorder caused by a repetition over 200 times of the CGG trinucleotide situated in the 5=-untranslated region of the fragile X mental retardation 1 gene (FMR1). The interval between 55 and 199 CGG repeats, which is over the normal range but below full mutation, is named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The hyperresponsive behavior is thought to be related to a lack of GABA inhibition which causes a lack of habituation to sensory stimuli seen in children with FXS [58]. GABA deficits have not only been documented in FXS but also in those with the premutation [59]. …”
Section: Discussionmentioning
confidence: 99%
“…The hyperresponsive behavior is thought to be related to a lack of GABA inhibition which causes a lack of habituation to sensory stimuli seen in children with FXS [58]. GABA deficits have not only been documented in FXS but also in those with the premutation [59]. …”
Section: Discussionmentioning
confidence: 99%
“…12 Deficits in FMRP lead to up-regulation of the mGluR5 system 33 and down-regulation of the GABA A system, 34 resulting in an excitatory/inhibitory imbalance that is observed in the premutation mouse-model neurons. 35 In this regard, a recent transcranial magnetic stimulation (TMS) study 36 demonstrated that asymptomatic adult women with the premutation have reduced GABA A -mediated intracortical and afferent inhibition from the cerebellum to the primary motor cortex, compared to age-matched controls. It is possible that these GABA A deficits predispose carriers to the ADHD symptoms experienced by approximately 30% of boys with the premutation.…”
Section: Neurodevelopmental Problems Associated With the Premutationmentioning
confidence: 99%
“…The observation that allopregnanolone normalizes network activity in neurons cultured from premutation mice, 35 coupled with the observed GABA A deficit in FXTAS patients, 36 suggests that a GABA A agonist will be beneficial to those with FXTAS. Moreover, at the cellular level, an mGluR5 antagonist similarly improved neuronal network activity, 35 pointing to an excitatory/inhibitory imbalance that is reminiscent of FXS.…”
Section: Treatment Of Fxtasmentioning
confidence: 99%
“…For instance, lack of FMRP found in the mouse model of FXS leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in FXS patients (Koekkoek et al, 2005). Indeed, although premutation carriers of FMRP lead to a different syndrome (FXTAS), they showed an absence of cerebellar inhibition over primary motor cortex and a reduced GABA-mediated intracortical and afferent inhibition compared with healthy individuals (Conde et al, 2013) that could potentially also be present in FXS patients. Moreover, FXS patients display specific emotion recognition deficits for angry and neutral (but not happy or fearful) facial expressions through visual scanning tasks (Shaw and Porter, 2013), that in turn is directly related to formation and function of neuronal circuits attributed to behavioral processes such as fear, emotion recognition and anxiety carried out by the amygdala (Olmos-Serrano and Corbin, 2011; Kim et al, 2014).…”
Section: Cognition and Behavioral Processing In Fxsmentioning
confidence: 99%